2016
DOI: 10.1021/acsami.6b09026
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ZT of InxCo4Sb12–InSb Nanocomposites Fabricated by Hydrothermal Synthesis Combined with Solid–Vapor Reaction: A Signature of Phonon-Glass and Electron-Crystal Materials

Abstract: A rapid route of synthesizing pristine CoSb at relatively low temperature was previously developed. However, filling the voids using the same procedure is not successful. We develop a new route to fabricate In-filled cobalt skutterudites with InSb nanoinclusions InCoSb-(InSb) via solid-vapor reaction between hydrothermally synthesized CoSb powder and the indium chunk. The nanocomposites are characterized using powder X-ray diffraction, field-emission scanning electron microscopy, transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 64 publications
0
14
1
Order By: Relevance
“…The improvement of mobility with doping is inconsistent with the traditional transport scenario, in which the carrier mobility usually decreases with doping due to the increased impurity scattering . Recently, similar abnormal phenomena have been observed in several other thermoelectric systems, and different scenarios have been proposed to explain this elusive behavior, such as modulation doping, , tuning the carrier scattering mechanism, and improving the grain boundary connectivity by a second phase. In the modulation doping picture, the charge carriers transfer from the doped grains to the undoped grains, which enhances the mobility in comparison to uniform doping samples, but the mobility is still lower than that of the undoped samples. , Shuai et al reported that, by codoping with Te and Nb, the carrier scattering mechanism of Mg 3 Sb 2 -based materials can be tuned from ionization scattering to mixed scattering (between ionization and acoustic phonon scattering), which can improve the mobility from 19 to 77 cm 2 V –1 s –1 . It is worth noting that, in the Mg 3 Sb 2 case, the carrier concentration decreases after doping, wheareas, in our V-doped MoS 2 samples, the carrier concentration increases with doping.…”
Section: Resultsmentioning
confidence: 98%
“…The improvement of mobility with doping is inconsistent with the traditional transport scenario, in which the carrier mobility usually decreases with doping due to the increased impurity scattering . Recently, similar abnormal phenomena have been observed in several other thermoelectric systems, and different scenarios have been proposed to explain this elusive behavior, such as modulation doping, , tuning the carrier scattering mechanism, and improving the grain boundary connectivity by a second phase. In the modulation doping picture, the charge carriers transfer from the doped grains to the undoped grains, which enhances the mobility in comparison to uniform doping samples, but the mobility is still lower than that of the undoped samples. , Shuai et al reported that, by codoping with Te and Nb, the carrier scattering mechanism of Mg 3 Sb 2 -based materials can be tuned from ionization scattering to mixed scattering (between ionization and acoustic phonon scattering), which can improve the mobility from 19 to 77 cm 2 V –1 s –1 . It is worth noting that, in the Mg 3 Sb 2 case, the carrier concentration decreases after doping, wheareas, in our V-doped MoS 2 samples, the carrier concentration increases with doping.…”
Section: Resultsmentioning
confidence: 98%
“…zT of 1.5 was observed in n-type Yb y Co 4 Sb 12, and zT of 1.06 was found in p-type Ce y Fe 3 CoSb 12 by introducing multilayer graphene into grain boundaries of these skutterudites [108]. zT of 1.0 was achieved in In 0.04 Co 4 Sb 12 -(InSb) 0.05 nanocomposite at 575 K which is highest for cobalt skutterudites at T575 K containing single filler of In because of the reduced thermal conductivity and high electrical conductivity as compared to pristine Co 4 Sb 12 [109]. Lattice thermal conductivity is reduced due to high phonon scattering at the InSb nano-inclusions, and electrical conductivity is increased due to the high mobility of InSb [109].…”
Section: Skutteruditesmentioning
confidence: 98%
“…zT of 1.0 was achieved in In 0.04 Co 4 Sb 12 -(InSb) 0.05 nanocomposite at 575 K which is highest for cobalt skutterudites at T575 K containing single filler of In because of the reduced thermal conductivity and high electrical conductivity as compared to pristine Co 4 Sb 12 [109]. Lattice thermal conductivity is reduced due to high phonon scattering at the InSb nano-inclusions, and electrical conductivity is increased due to the high mobility of InSb [109]. Khan et al reported a porous architecture of skutterudites containing nano-to micro-sized, irregularly shaped and randomly oriented phonons to scatter a broad spectrum of phonons without employing the conventional rattling structure hence the zT of 1.6 was obtained in the nano-micro porous architecture Co 23.4 Sb 69.1 Si 1.5 Te 6 alloy which is highest reported for any unfilled skutterudite [106].…”
Section: Skutteruditesmentioning
confidence: 99%
“…Organic solid-state fluorescent materials have received widespread attention owing to their remarkable properties and promising optoelectronic applications in the fields of organic light-emitting diodes (OLED), lasers, sensors, displays, data storage, hiding, and bioimaging. Organic fluorescent crystals have developed rapidly in recent years. With continuous development and in-depth research by crystallography, scientists have fully understood the key factors that determine the fluorescence of organic molecules in the solid state, which include intermolecular interactions, molecular conformations and molecular stacking modes. Current methods to prepare organic fluorescent crystals usually involve two steps: (1) solution phase organic synthesis and (2) crystallization of target fluorescent compounds. Although these steps are useful, the use of large amounts of organic solvents not only increases the overall cost but also restricts the study of the crystal-to-crystal transformation mechanism. , To avoid these potential drawbacks, direct transformation of nonfluorescent organic crystals into fluorescent organic crystals by chemical postsynthetic modification (PSM) might be an alternative.…”
Section: Introductionmentioning
confidence: 99%